Evaluasi Determinan Keaktifan Kader Dalam Pelaksanaan Pos Pelayanan Terpadu (POSBINDU) Penyakit Tidak Menular (PTM) Tahun 2023 - Widya Kaharani Putri; Dily Ekasari; Lina Alfiyani; Anindita Hasniati Rahmah; Arifin Arifin; Moh Tri Zainudin (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2024)
Non communicable diseases are currently a major health problem and the biggest cause of death in the world. This study aims to identify the determinants of cadre activity in the implementation of the Non-Communicable Disease Posbindu in Margomulyo village. Integrated coaching post for early detection of community-based Non-Communicable Disease (NCD) risk factors. The activeness of cadres which is the cornerstone of the running of the PTM posbindu plays an important role. This research uses a qualitative approach with a case study method in Margomulyo village. Data in this study were obtained through interviews, observation and document analysis. The results showed that the determinants that affect cadre activity are knowledge, cadre education, cadre work, cadre motivation, length of time as cadres and cross-sector support in the implementation of the PTM Posbidu program. This research can be used as a reference for increasing cadre activity in Margomulyo village by increasing determinants that have a significant effect on activeness.